Superconductivity in Alkaline Earth Metal-Filled Skutterudites BaxIr4X12 (X = As, P) - Qi, Yanpeng; Lei, Hechang; Guo, Jiangang; Shi, Wujun; Yan, Binghai; Felser, Claudia; Hosono, Hideo (Journal of the American Chemical Society, 2017)
We report superconductive iridium pnictides BaxIr4X12 (X = As and P) with a filled skutterudite structure, demonstrating that Ba filling dramatically alters their electronic properties and induces a nonmetal-to-metal transition with increasing the Ba content x. The highest superconducting transition temperatures are 4.8 and 5.6 K observed for BaxIr4As12 and BaxIr4P12, respectively. The superconductivity in BaxIr4X12 can be classified into the Bardeen-Cooper-Schrieffer type with intermediate coupling.
CRIS-Team Scopus Importer:2022-04-14